Research on Digital Preservation and Innovative Dissemination of Ezhou Bronze Mirror Culture from the Perspective of AI-Enhanced Interactive Virtual Reality - Zhou, Bianyu (Innovative Applications of AI, 2026)
As a gem of ancient Chinese bronze art, Ezhou bronze mirrors face challenges in preservation and dissemination such as the fragility of the physical objects, monotonous display methods, and difficulties in interpreting and perceiving their deep cultural connotations. The integration of Artificial Intelligence (AI) and Interactive Virtual Reality (IVR) technology opens new pathways for the deep revitalization and innovative transmission of cultural heritage. Based on an analysis of the cultural value of Ezhou bronze mirrors, this paper elaborates on the transformative advantages of the AI-VR fusion in constructing immersive, intelligent, and personalized cultural experiences. Through feasibility analysis, the paper constructs a digital preservation and dissemination strategy system with AI as its core engine, proposing three key modules: "AI-Powered Ornament Decoding and Immersive Narration", "Intelligent Simulation of Craftsmanship and Interactive Learning", and "AIGC-Driven Dynamic Dissemination and Cultural Creative Derivative Development". The proposed system aims to establish a digital ecosystem that integrates intelligent preservation, in-depth education, and cross-border dissemination, providing an innovative solution for the "living" transmission and value regeneration of Ezhou bronze mirror culture in the digital age.